2009
DOI: 10.1213/ane.0b013e3181b6496a
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Postoperative Throat and Neck Complaints After the Use of the i-gel® and the La Premiere® Disposable Laryngeal Mask: A Double-Blinded, Randomized, Controlled Trial

Abstract: In this randomized study, the i-gel supraglottic device resulted in a lower incidence of throat and neck complaints than the La Premiere LM airway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
40
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(46 citation statements)
references
References 7 publications
5
40
1
Order By: Relevance
“…The postoperative complaints in our study demonstrated a lower incidence of postoperative sore throat and difficulty swallowing at 24h in the i-gel TM group. Very similar results were experienced in another study where the i-gel TM caused lower incidence of postoperative sore throat and neck complaints 24 . This fact may be attributed to the different pressures exerted on pharyngeal mucosa by the inflated cuff of the laryngeal mask compared with the cufless anatomical shape of the i-gel TM .…”
supporting
confidence: 84%
“…The postoperative complaints in our study demonstrated a lower incidence of postoperative sore throat and difficulty swallowing at 24h in the i-gel TM group. Very similar results were experienced in another study where the i-gel TM caused lower incidence of postoperative sore throat and neck complaints 24 . This fact may be attributed to the different pressures exerted on pharyngeal mucosa by the inflated cuff of the laryngeal mask compared with the cufless anatomical shape of the i-gel TM .…”
supporting
confidence: 84%
“…Previous studies showed that the i-gel resulted in a lower incidence of throat and neck complaints than that of other LMAs [17].…”
Section: Discussionmentioning
confidence: 82%
“…The use of the i-gel has now been shown clinically to result in fewer postoperative sore throat and neck complaints compared with disposable LMAs [19]. Although our study was not powered to examine airway complications or morbidity, bloodstaining on removal was found in one i-gel (2%) and two (4%) LMA Supremes.…”
Section: Discussionmentioning
confidence: 83%